2013
DOI: 10.1378/chest.12-2058
|View full text |Cite
|
Sign up to set email alerts
|

Lumican Regulates Ventilation-Induced Epithelial-Mesenchymal Transition Through Extracelluar Signal-Regulated Kinase Pathway

Abstract: A cute lung injury (ALI) and its most severe manifestation, ARDS, are characterized by an initial inhomogeneous infl ammatory reaction or epithelial injury that is followed by fi broblast proliferation and extracellular matrix (ECM) accumulation. 1,2 Mechanical ventilation is required for life support in patients with ARDS; however, the potential for overdistension of the healthy parts of the lungs is great. Ventilatorinduced lung injury (VILI) is characterized by noncardiogenic pulmonary edema; release of inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 34 publications
3
19
0
Order By: Relevance
“…Type I collagen is more prevalent in the late‐phase of ALI, whereas type III collagen fibre, which is relatively more flexible and susceptible to breakdown, predominates in the early stage of ALI . Furthermore, mechanical forces can modify the gene expression and structural remodelling of ECM through increased transpulmonary pressure, heterogeneous distribution of ventilation, increased tissue stretch, reduced pulmonary lymphatic drainage and direct secretion of various growth factors, including TGF‐β1 . We demonstrated that high tidal volume MV increased oxidative stress, collagen accumulation and increase of collagen 1a gene expression.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Type I collagen is more prevalent in the late‐phase of ALI, whereas type III collagen fibre, which is relatively more flexible and susceptible to breakdown, predominates in the early stage of ALI . Furthermore, mechanical forces can modify the gene expression and structural remodelling of ECM through increased transpulmonary pressure, heterogeneous distribution of ventilation, increased tissue stretch, reduced pulmonary lymphatic drainage and direct secretion of various growth factors, including TGF‐β1 . We demonstrated that high tidal volume MV increased oxidative stress, collagen accumulation and increase of collagen 1a gene expression.…”
Section: Discussionmentioning
confidence: 79%
“…This transition features the loss of epithelial markers (E‐cadherin and aquaporin‐5) and apical–basal polarity as well as cytoskeletal rearrangement, transition to a spindle‐shaped morphology and the acquisition of mesenchymal markers (α‐smooth muscle actin (α‐SMA) and N‐cadherin) . Furthermore, MV can induce EMT and thus initiate and propagate VILI‐associated lung fibrosis . The Src protein tyrosine kinase is expressed by leucocytes, alveolar epithelial cells, endothelial cells and fibroblasts in the lung.…”
Section: Introductionmentioning
confidence: 99%
“…Imbalance between oxidant production and antioxidant protection results in accumulation of ROS oxidants may contribute to the development of pulmonary fibrosis due to their effects on the production of TGF-β (Li et al 2013), suggesting that using antioxidants may be helpful in the prevention, and perhaps the treatment of fibrosis in VILI.…”
Section: Discussionmentioning
confidence: 99%
“… 3 A large proportion of data implicates that epithelial cells undergoing the process of epithelial-mesenchymal transition (EMT) is one source of fibroblasts. 4 , 5 During EMT, epithelial cells gradually lose their epithelial characteristics and transform into a mesenchymal-like cell phenotype, which begins to synthesize the components of ECM, such as collagen I and fibronectin. Among the extracellular cytokines that activate EMT, transforming growth factor β (TGF-β) is known to be the main inducer.…”
Section: Introductionmentioning
confidence: 99%